Down syndrome in Africa: Challenges, opportunities, and future directions - Mc Glinchey, Eimear (My University, 2025)
INTRODUCTION: As life expectancy improves for people with Down syndrome (DS) in Africa, the risk of developing DS-associated Alzheimer’s disease (DSAD) will rise. There is a pressing need to plan for this emerging challenge, particularly in the context of existing health and social disparities. METHODS: This work emerged from a pan-African collaboration, including discussions at the Brain Ageing and Dementia in Low- and Middle-Income Countries conference held in Nairobi in 2024, where stakeholders identified regional priorities for DS and dementia care. RESULTS: Limited epidemiological, cognitive, biomarker data, delayed diagnoses, and gaps in specialized services may impact access to care. However, innovative solutions, such as mobile biomarker sampling and culturally adapted cognitive assessments, offer promising strategies. DISCUSSION: Integrating global advances in DSAD research with Africa’s strengths in community-based care offers opportunities. By prioritizing research, capacity building, and health system integration, this work advocates for the inclusion of DS in Africa’s dementia strategies.
PUBLISHED
Keywords: Africa; Alzheimer’s disease; Down syndrome; equity; Global South; Ageing